Behavior of borate complex anion on the stabilities and the hydrogen evolutions of ZnxCo3−xO4 decorated graphene. (June 2015) - Hao, Xuqiang; Jin, Zhiliang; Wang, Fang; Xu, Jing; Min, Shixiong; Yuan, Hong; Lu, Gongxuan
Highlights: The stabilities and hydrogen evolutions were improved with the addition of borate. The synergetic effects were due to the electrons transfer. The borate contribute to the more efficiently capture electron. Abstract: The electron oscillation of borate complex anions in the borate solution was a very interesting peculiar phenomenon in the study of Solution Chemistry up to now. By means of borate complex anions addition, reacting system inertion and the electrons addition, based on the peculiar contribution of borate complex anions with an electron oscillation characters, the stabilities and the hydrogen evolutions of Zn x Co3 − x O4 decorated graphene were greatly improved. Here, the photocatalytic activity was dependent on the synergetic effects of borate complex anions and graphene. The structure–activity relationships between the borate complex anions and the Zn x Co3 − x O4 decorated grapheme were investigated. The borate complex anions can not only contribute to the more efficiently capture electrons from excited Eosin dye but also beneficial to the more efficiently transfer electrons to the decorated catalysts. So the charge separation and the electrons transfer were more efficient in the condition of the borate complex anions addition as supported by fluorescence studies. The synergetic effects between boron and grapheme were due to the double-pathway of synergetic effects for electrons transfer.